OpenJDK cookbook : over 80 recipes to build and extend your very own version of Java platform using OpenJDK project /: over 80 recipes to build and extend your very own version of Java platform using OpenJDK project. (2015) - Kasko, Alex; Kobylyanskiy, Stanislav; Mironchenko, Alexey
No abstract available